Characterization of the Reasons Why Brazilian Science Teachers Drop Out of Online Professional Development Courses - Luz, Maurício Roberto Motta Pinto da; Rolando, Luiz Gustavo Ribeiro; Salvador, Daniel Fábio; Sousa, André (International Review of Research in Open and Distributed Learning, 2018)
Teachers face different challenges and opportunities through distance education. We used a combination of quantitative and qualitative approaches to investigate the factors leading in-service science teachers to quit online courses. No differences were found between persistent and drop-out teachers based on their sociodemographic data and their technological skills. The dropout rates were unrelated to courses’ contents or duration. A follow-up procedure revealed that a heavy workload and technological issues accounted for most of the reasons teachers left courses. We conclude that financial incentives and reduced workload are key factors that could minimize attrition and increase persistence among Brazilian teachers.